2016
DOI: 10.1007/s10903-015-0245-6
|View full text |Cite
|
Sign up to set email alerts
|

Surviving the Distance: The Transnational Utilization of Traditional Medicine Among Oaxacan Migrants in the US

Abstract: Transnational health practices are an emergent and understudied phenomenon, which provide insight into how migrants seek care and tend to their health care needs in receiving communities. We conducted in depth interviews with return migrants (N = 21) and traditional healers (N = 11) to explore transnational health practices among Mixtec migrants from Oaxaca, specifically in relation to their utilization of traditional healers, medicinal plants, and folk remedies. In established migrant destination points, folk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 20 publications
2
16
0
Order By: Relevance
“…Consistent with previous studies (Barragan et al 2011; Barron et al 2004; Gonzalez-Vazquez et al 2016; Mittman et al 1998; Penn et al 2010; Shaw and Hurst 2008; Solomon et al 2012), there was a duality to their worldview which took into account both Western medicine and traditional medicine beliefs. They stated that they believed what the treating physicians had said during the many discussions regarding the natural history of their child’s inborn error of metabolism, and while critically ill in the PICU.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Consistent with previous studies (Barragan et al 2011; Barron et al 2004; Gonzalez-Vazquez et al 2016; Mittman et al 1998; Penn et al 2010; Shaw and Hurst 2008; Solomon et al 2012), there was a duality to their worldview which took into account both Western medicine and traditional medicine beliefs. They stated that they believed what the treating physicians had said during the many discussions regarding the natural history of their child’s inborn error of metabolism, and while critically ill in the PICU.…”
Section: Resultssupporting
confidence: 86%
“…During the final genetic counseling session, the two families of patients A1, A2, and A3 were more open about their thought processes and solicitation of additional medical advice during the clinical presentation of symptoms, disease diagnosis, and hospitalization ultimately resulting in each child's death. Consistent with previous studies (Barragan et al 2011;Barron et al 2004;Gonzalez-Vazquez et al 2016;Mittman et al 1998;Penn et al 2010;Shaw and Hurst 2008;Solomon et al 2012), there was a duality to their worldview which took into account both Western medicine and traditional medicine beliefs. They stated that they believed what the treating physicians had said during the many discussions regarding the natural history of their child's inborn error of metabolism, and while critically ill in the PICU.…”
Section: Traditional Medicine Beliefssupporting
confidence: 86%
See 2 more Smart Citations
“…They perceived that sobador knowledge and skill varied widely; knowledge about sobador quality is therefore important. Although not in reference to sobadores , researchers have reported that Latinos living in other regions of the United States note the importance of determining traditional healers’ skill and knowledge [3436]. Participants considered doctors to be professionals due to their access to crucial technology such as X-ray machines, and advanced education.…”
Section: Discussionmentioning
confidence: 99%